If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 = 1 + -2a Solving 35 = 1 + -2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2a' to each side of the equation. 35 + 2a = 1 + -2a + 2a Combine like terms: -2a + 2a = 0 35 + 2a = 1 + 0 35 + 2a = 1 Add '-35' to each side of the equation. 35 + -35 + 2a = 1 + -35 Combine like terms: 35 + -35 = 0 0 + 2a = 1 + -35 2a = 1 + -35 Combine like terms: 1 + -35 = -34 2a = -34 Divide each side by '2'. a = -17 Simplifying a = -17
| -41=2x-7 | | -5(6y-9)-y=-2(y-4) | | 4(x-3)=6(x+1) | | -2(5x-1)=11 | | n^2+5=105 | | -7x+24=8+x | | (2b-5)(2b+5)= | | -3-8(3-2k)=-155 | | -2x^2=-76 | | 2.5(+-2)-6=9 | | 5x-5(2-2x)=-10 | | x-5+4=9 | | 2-6x=10-2x | | 10x+24(x-3)=336 | | 25-15+14=x | | g(t)=36000-1500t | | x-.75x=190 | | 6[x-(9x-6)]=4-5x | | x-7x=18 | | 3x-12(3+x)-4x=-(-5-x)-(7-1) | | 2x+2=-4x-16 | | y+y+2=-16 | | 14=7x+5 | | n+3+5=-6 | | 180=37x-13 | | 7+2/3x=13 | | 4x+21x=-119 | | 63=n+28 | | 5x-2-3-x+2=9 | | x(x+9)=x^2+15x+12 | | 25-15+14= | | 6x-7=7+4x |